Ultra-sensitive protein detection with organic electrochemical transistors printed on plastic substrates - Macchia, Eleonora; Romele, Paolo; Manoli, Kyriaki; Ghittorelli, Matteo; Magliulo, Maria; Kovács-Vajna, Zsolt M; Torricelli, Fabrizio; Torsi, Luisa (Flexible and printed electronics, 2018)
The detection of protein biomarkers is of great importance in the early diagnosis of severe pathological states. Although in the last decade many approaches to achieve ultra-sensitive protein detection have been developed, most of them require complicated assay set-ups, hindering their adoption in point-of-care applications and on-spot diagnosis. Here we show an organic electrochemical transistor (OECT) biosensor printed on plastic substrates that can selectively detect Immunoglobulin G (IgG) with an unprecedented attomolar detection limit. The OECT is used as a transducer of the biorecognition event taking place at the gate electrode. The measured concentrations are well below the detectable limits of the leading clinical diagnostic enzyme-linked immunosorbent assay, and comparable to the ones gathered with the label-needing single molecule arrays platform. Our work benchmarks the role of plastic OECT-based biosensors as a powerful tool in simple, low cost, yet non-invasive, ultra-sensitive, and widely applicable immunoassay technology.